The Essence Of Patriotical Education Of Youth - Khamdamov, Alisher Samijonovich (TLEP – International Journal of Multidiscipline, 2025)
This article analyzes the theoretical foundations, pedagogical aspects and modern approaches to educating young people in the spirit of patriotism. The study examines the content, forms and methods of patriotic education, and also substantiates the importance of educating the younger generation as patriots in the context of national values and modern globalization. The results of the study show that for effective patriotic education, joint activities of educational institutions, family and society are necessary.